FOREIGN DIRECT INVESTMENT AND ECONOMIC GROWTH: ADYNAMIC STUDY OF MEASUREMENT APPROACHES AND RESULTS (World Economics and Finance Bulletin, 2023)
The relationship between foreign direct investment and economicgrowth (FDIEG) has been subject to extensive research. The firstdocument related to FDIEG research in Web of Science was pub-lished in 1992 so that the research time is close to 30 years. Thisarticle aims to make a bibliometric study to measure the FDI-EGresearch from different points of view. 1,075 documents withrespect to FDI-EG research were collected, and a strong bibliomet-ric analysis was carried out by Bibliometrix software and review of approaches. from the “enemy” is undesirable, as it was during the cold war.
Keywords: Foreign direct investment; economic growth; the United States; Investment